Role-playing games and simulations in teaching French - Nazirova , Ozoda (The Lingua Spectrum, 2025)
This diploma project work is devoted to the study of the theoretical foundations of role-playing games and simulations in teaching French, as well as methods of their practical organization. The work deeply analyzes the theoretical, didactic and psychological aspects of using role-playing games and simulations in language teaching. The study determined the effectiveness of these interactive methods in developing students’ speaking skills when learning French, and also showed the potential for significantly increasing students’ language proficiency and motivation. Based on the results of the work, methodological recommendations were developed for organizing role-playing games and simulations and assessing their effectiveness.